Analysis of Sustainable Strategies in Multinational Companies in Mexico: Development Towards a Circular Supply Chain - Nava-Aguirre, Karla Maria (2023)
In recent decades companies have used linear models in their daily operations, creating products with a short life cycle. Increasing waste emissions have caused environmental problems that create permanent and negative effects in communities. In 2022, the Mexican state of Nuevo León issued 7 environmental alerts due to high levels of pollution within the metropolitan area. This study aims to analyze the sustainable strategies implemented in the Circular Supply Chain (CSC) of the multinational leading companies in Nuevo León, Mexico, to identify sustainable strategies in companies and determine ways to measure the strategies previously mentioned. Forbes’ book Empresas líderes (2022) was used to select the companies for this study. Based on the findings, 6 strategies are proposed to integrate a CSC in businesses and it is concluded that multinationals must implement the decarbonization of operations, from which various alternatives arise such as eco-design and business symbiosis.